The Business Network Analysis of Anita Bakery MSMEs in Distributing Their Products to Store - Karlina Fitriani; Nova Kardina; Salamatur R obiah; Osi Lestari (PT ARFA DIGITAL TECHNOLOGY, 2025)
Business networks are an important element in developing a business, especially for MSME actors. This study aims to determine the role of business networks in the sustainability of Anita Bakery which has been operating for 10 years. This study uses a qualitative approach and direct interviews with business owners, the results of the study show that Anita Bakery spreads its products to local stalls and has a strong business network with suppliers, stall partners, and sales. Even though it does not use online marketing, Anita Bakery is able to survive and grow thanks to the established business network. These findings confirm that business networks play a significant role in maintaining operational stability, facing competition, and improving the sustainability of MSME businesses in a sustainable manner.